Racial/Ethnic and Income Disparities in the Prevalence of Comorbidities that Are Associated With Risk for Severe COVID-19 Among Adults Receiving HIV Care, United States, 2014–2019. (1st March 2021) - Weiser, John K.; Tie, Yunfeng; Beer, Linda; Neblett Fanfair, Robyn; Shouse, Roy Luke
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Health inequities among people with HIV may be compounded by disparities in the prevalence of comorbidities associated with an increased risk of severe illness from COVID-19. Setting: Complex sample survey designed to produce nationally representative estimates of behavioral and clinical characteristics of adults with diagnosed HIV in the United States. Methods: We estimated the prevalence of having ≥1 diagnosed comorbidity associated with severe illness from COVID-19 and prevalence differences (PDs) by race/ethnicity, income level, and type of health insurance. We considered PDs ≥5 percentage points to be meaningful from a public health perspective. Results: An estimated 37.9% [95% confidence interval (CI): 36.6 to 39.2] of adults receiving HIV care had ≥1 diagnosed comorbidity associated with severe illness from COVID-19. Compared with non-Hispanic Whites, non-Hispanic Blacks or African Americans were more likely [adjusted PD, 7.8 percentage points (95% CI: 5.7 to 10.0)] and non-Hispanic Asians were less likely [adjusted PD, −13.7 percentage points (95% CI: −22.3 to −5.0)] to have ≥1 diagnosed comorbidity after adjusting for age differences. There were no meaningful differences between non-Hispanic Whites and adults in other racial/ethnic groups. Those with low income were more likely to have ≥1 diagnosed comorbidity [PD, 7.3 percentage points (95% CI: 5.1 to 9.4)]. Conclusions: Among adults receiving HIV care, non-Hispanic Blacks and those with low income were more likely to have ≥1 diagnosed comorbidity associated with severe COVID-19. Building health equity among people with HIV during the COVID-19 pandemic may require reducing the impact of comorbidities in heavily affected communities.